2009
DOI: 10.1111/j.1525-142x.2009.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of arthropod midline netrin accumulation revealed with a cross‐reactive antibody provides evidence for midline cell homology

Abstract: SUMMARY Although many similarities in arthropod CNS development exist, differences in axonogenesis and the formation of midline cells, which regulate axon growth, have been observed. For example, axon growth patterns in the ventral nerve cord of Artemia franciscana differ from that of Drosophila melanogaster. Despite such differences, conserved molecular marker expression at the midline of several arthropod species indicates that midline cells may be homologous in distantly related arthropods. However, data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
(95 reference statements)
2
31
0
Order By: Relevance
“…We find that in A. aegypti, unique among the insects studied to date, sim and a number of additional genes expressed in the Drosophila midline are expressed in the lateral CNS rather than the midline in the late embryo. Despite this change, both D. melanogaster and A. aegypti retain what appear to be structurally and functionally homologous CNS midlines (Clemons et al, 2011; Simanton et al, 2009), including with respect to genes expressed in differentiated midline cells. We identify CRMs for several of the affected A. aegypti genes and test their function in transgenic Drosophila, where they drive a D. melanogaster-like pattern of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…We find that in A. aegypti, unique among the insects studied to date, sim and a number of additional genes expressed in the Drosophila midline are expressed in the lateral CNS rather than the midline in the late embryo. Despite this change, both D. melanogaster and A. aegypti retain what appear to be structurally and functionally homologous CNS midlines (Clemons et al, 2011; Simanton et al, 2009), including with respect to genes expressed in differentiated midline cells. We identify CRMs for several of the affected A. aegypti genes and test their function in transgenic Drosophila, where they drive a D. melanogaster-like pattern of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The study of conservation and divergence of developmental genetic mechanisms has provided enormous insight into the evolutionary history of animals, from establishing body axes to formation and patterning of the nervous system. Studies of neural differentiation and the initial formation of axon pathways in arthropods and related animals have provided a glimpse into the variety of neurodevelopmental mechanisms at work in this group (Duman-Scheel et al, 2007; Fischer and Scholtz, 2010; Linne and Stollewerk, 2011; Mayer and Whitington, 2009; Simanton et al, 2009; Stollewerk and Eriksson, 2010; Ungerer et al, 2011). Intriguingly, a recent analysis of axon pathway formation in onychophorans (worm-like relatives of arthropods with unsegmented bodies and unjointed legs) suggested that increasingly precise control of axon guidance may have been crucial to the evolution of the modern arthropod nervous system by facilitating intersegmental coordination between limb and body muscles (Mayer and Whitington, 2009; Whitington and Mayer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been argued that the ventral midline in Parhyale and Drosophila are homologous structures (Simanton et al, 2009). The experimental results showing that Ph-sim specifies the midline fate in Parhyale supports this idea and further suggests that this developmental role of sim dates back to at least the last common ancestor of insects and malacostracan crustaceans.…”
Section: Evolution Of Midline Function and DV Patterning In Arthropodsmentioning
confidence: 99%
“…Nonmidline ectoderm is derived from three ectodermal blastomeres (EL, ER and EP), whereas midline ectoderm is derived predominantly from EP (Gerberding et al, 2002). Finally, despite the divergent developmental origins of the ventral midline in Parhyale and Drosophila, the presence of common molecular markers has been used to argue that they are homologous structures (Simanton et al, 2009;Duman-Scheel and Patel, 1999).…”
Section: Introductionmentioning
confidence: 99%